Application of environmental accounting tools for agricultural companies - Hoffmann, András; Somogyi, Tamás (Acta Agraria Debreceniensis, 2006)
Today there is an ever stronger requirement for companies to consider the environmental aspects of their operation. The incorporation of these aspects into the economic practise of agricultural firms in our country is still in its infancy and, moreover, it usually follows from outside coercion (legal regulation) rather than voluntary behaviour. Consequently, in the Hungarian agrar-economics – contrary to the example of Western Europe – the application of environmental accounting in agriculture is a barely researched subject; this has been so even though the environmental policy of companies can be made more conscious by adding an environmental dimension to the organizational information systems. The aim of our investigation is two-fold. The first goal is to form a method that quantifies the environmental load of companies, is capable of comparing environmental performance of companies with different sizes, and takes into account the specific attributes of agriculture as well. The second is to apply this method in practice, to prove that estimating the environmental load of companies is possible by processing already available data (fiscal, accounting and statistical) using new concepts. In this publication we present the joint application of three methods – each belonging to the toolset of environmental accounting – for two companies dealing with both crop and animal farming in the Pannonian region. The three methods are partly built upon each other and partly complementary. The company-level environmental balance is capable to show the relations between a given firm and its surrounding, but realistic comparison between environmental performance of different companies or periods is only possible by using specific index quantities.